Serotype, mating type and ploidy of Cryptococcus neoformans strains isolated from patients in Brazil - Misako OHKUSU; Naomi TANGONAN; Kanji TAKEO; Eriko KISHIDA; Masami OHKUBO; Shigeji AOKI; Kenjiro NAKAMURA; Takaaki FUJII; Isadora C. de SIQUEIRA; Elves A.P. MACIEL; Sumire SAKABE; Gisele M.D. ALMEIDA; et al. (Universidade de São Paulo (USP), 2002)
Serotype, mating type and ploidy of 84 strains of Cryptococcus neoformans isolated from 61 AIDS and 23 non-AIDS patients admitted in a tertiary teaching hospital in São Paulo, Brazil were examined. Among 61 strains isolated from AIDS patients, 60 strains were var. grubii (serotype A). Only one strain was var. gattii (serotype B). No var. neoformans (serotype D) was found. Among 23 strains isolated from non-AIDS patients, 15 were var. grubii (serotype A) and the remaining 8 were var. gattii, all of which were serotype B. Seventy-three of the 75 serotype A strains were the heterothallic alpha type (MATalpha) and the remaining 2 were untypable (asexual). Most of the MATalpha strains (69/73) were haploid and the remaining 4 strains were diploid. Similarly, both of the 2 asexual strains among the 75 serotype A strains were haploid. There were no alpha-mating type (MATalpha) strains among the 84 isolates. All of the 8 var. gattii strains were serotype B and haploid. Among a total of 84 strains tested, neither serotype AD nor serotype D were found. Neither triploid nor tetraploid were found. These results suggest that the serological, sexual and ploidy characteristics in C. neoformans strains isolated from AIDS patients in São Paulo were rather simple, whereas strains isolated from non-AIDS patients presented serotype A and B with predominance of serotype A.